Observations of storm time midlatitude ion‐neutral coupling using SuperDARN radars and NATION Fabry‐Perot interferometers. Issue 10 (24th October 2015) - Joshi, P. P.; H. Baker, J. B.; Ruohoniemi, J. M.; Makela, J. J.; Fisher, D. J.; Harding, B. J.; Frissell, N. A.; Thomas, E. G.
Abstract: Ion drag is known to play an important role in driving neutral thermosphere circulation at auroral latitudes, especially during the main phase of geomagnetic storms. During the recovery phase, the neutrals are known to drive the ions and generate ionospheric electric fields and currents via the disturbance dynamo mechanism. At midlatitudes, the precise interplay between ions and neutrals is less understood largely because of the paucity of measurements that have been available. In this work, we investigate ion‐neutral coupling at middle latitudes using colocated ion drift velocity measurements obtained from Super Dual Auroral Radar Network radars and neutral wind velocity and temperature measurements obtained from the North American Thermosphere Ionosphere Observing Network (NATION) Fabry‐Perot interferometers. We examine one recent storm period on 2–3 October 2013 during both the main phase and late recovery phase. By using ion‐neutral momentum exchange theory and a time‐lagged correlation analysis, we analyze the coupling time scales and dominant driving mechanisms. We observe that during the main phase the neutrals respond to the ion convection on a time scale of ∼84 min which is significantly faster than what would be expected from local ion drag momentum forcing alone. This suggests that other storm time influences are important for driving the neutrals during the main phase, such as Joule heating. During the late recovery phase, the neutrals are observed to drive the ion convection without any significant time delay, consistent with the so‐called "neutral fly wheel effect" or disturbance dynamo persisting well into the late recovery phase. Key Points: Midlatitude ion‐neutral coupling is investigated using colocated SuperDARN‐NATION observations During the storm main phase, ion convection drives the neutrals on timescale of ∼84 min During the late recovery phase, neutrals drive the ion convection without any significant time delay